2022
DOI: 10.1111/hex.13429
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis management: Does the pharmacist play a role in bridging the gap between what patients actually know and what they ought to know? Insights from a national online survey

Abstract: Background: Guidelines encourage engagement in self-care activities for osteoarthritis (OA), but there are gaps in consumers' knowledge about suitable choices for self-care. Community pharmacists are in an ideal position to contribute to OA management through screening and supporting evidence-based pain management choices. Prior research established an association between health literacy and advice-seeking and appropriateness of analgesics choices (both lower in participants with limited health literacy) among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…As such, even if research is limited, an older adult with osteoarthritis may arguably suffer unduly because they are challenged in understanding what they need to do or why in order to remain in the community, rather than residing in a nursing home where their self-care role will be of less importance. As such, it appears reasonable to assert that if providers fail to appreciate COVID-19 implications, as well as the past social histories and ability to comprehend health messages of their older osteoarthritis clients, the capacity of the client for carrying out home based remedial approaches effectively and safely may be jeopardized [33,34,42] too challenged to decipher their health recommendations, or to contact their providers and seek advice, for example if they have limited feelings of confidence, or limited English language skills [36]. It appears therefore that a fair number of older adults with osteoarthritis may consequently fail to flourish even if they receive needed care if they fail to fully appreciate the importance of their lifestyle actions that are proven disease and disability predictors.…”
Section: Resultsmentioning
confidence: 99%
“…As such, even if research is limited, an older adult with osteoarthritis may arguably suffer unduly because they are challenged in understanding what they need to do or why in order to remain in the community, rather than residing in a nursing home where their self-care role will be of less importance. As such, it appears reasonable to assert that if providers fail to appreciate COVID-19 implications, as well as the past social histories and ability to comprehend health messages of their older osteoarthritis clients, the capacity of the client for carrying out home based remedial approaches effectively and safely may be jeopardized [33,34,42] too challenged to decipher their health recommendations, or to contact their providers and seek advice, for example if they have limited feelings of confidence, or limited English language skills [36]. It appears therefore that a fair number of older adults with osteoarthritis may consequently fail to flourish even if they receive needed care if they fail to fully appreciate the importance of their lifestyle actions that are proven disease and disability predictors.…”
Section: Resultsmentioning
confidence: 99%
“…UK policy recommendations to integrate pharmacists into LTC pathways and national workforce initiatives have promoted community pharmacy roles [16,17]. Community pharmacist roles have extended over the last twenty years beyond just supplying medicines and managing medicines-related problems into more 'cognitive services' that includes medicines optimisation [17][18][19][20][21]. Their role is now recognised as "supporting people with LTCs to improve their quality of life, health and wellbeing and to lead as independent a life as possible by supporting self-care" [22].…”
Section: Introductionmentioning
confidence: 99%
“…Given current government initiatives to enhance contact with pharmacies, supporting community pharmacy services to deliver better care to people with osteoarthritis is logical and needed. Similar initiatives are currently being explored in other countries [23][24][25], however, the expected role of community pharmacies in delivering osteoarthritis care, necessary support or pathways to provide this care, and patient and public awareness of the breadth of community pharmacy roles are not well understood/established in the United Kingdom [20,21]. Specifically, little is known about: what an enhanced community pharmacy role for osteoarthritis care should include, what support is needed to fulfil such a role, and whether it would be feasible to deliver and acceptable to community pharmacy teams.…”
Section: Introductionmentioning
confidence: 99%
“…Community pharmacy is increasingly viewed as a site for effective health interventions, such as health education, medication reviews, and vaccination. Greater utilisation of community pharmacy has been proposed as an opportunity to improve OA care (Briggs et al, 2018;McLachlan et al, 2022). A trial of pharmacist initiated care for knee OA in Canada found that this was effective and cost-effective (Marra et al, 2012(Marra et al, , 2014.…”
mentioning
confidence: 99%